Labour united and divided from the 1830s to the present - Avril, Emmanuelle; Béliard, Yann (Manchester University Press, 2018)
This work seeks to renew and expand the field of British labour studies, setting out new avenues for research so as to widen the audience and academic interest in the field, in a context which makes the revisiting of past struggles and dilemmas more pressing than ever.